Retinal vein occlusions, from basics to the latest treatment - Ho, Mary; Jonas, Jost B. (Retina, 2016)
Purpose: To review the pathophysiology, diagnosis, and updated treatments of retinal vein occlusions (RVOs). Methods: A review of the literature was performed, focusing on the epidemiology, pathophysiology, diagnosis, and treatments (including both medical and surgical treatments) of RVO. Based on this review, a comprehensive overview was provided regarding the topic of RVO and focused on recent treatment updates. Results: Retinal vein occlusions have an age- and sex-standardized prevalence of 5.20 per 1,000 for any RVO, 4.42 per 1,000 for branch RVO, 0.80 per 1,000 for central RVO. Worldwide, an estimated 16.4 million adults are affected by RVOs, with 2.5 million affected by central RVO and 13.9 million affected by branch RVO. Retinal vein occlusion is recognized as an important cause of blindness and the diagnostic approaches and treatment options for RVO are reviewed and reported. The current treatment options including medical treatments (bevacizumab, ranibizumab, aflibercept, triamcinolone, and dexamethasone implants) and surgical alternatives were reviewed and reported with summaries on the corresponding strength of evidence. Conclusion: Despite the understanding of this disease entity, challenges persist in the long-term treatment of RVO-related complications and visual loss. This review provided a detailed summary on the rationality and efficacy of recently developed treatment regimes and evaluated the potential benefit of combination therapy.